2011
DOI: 10.1002/art.30459
|View full text |Cite
|
Sign up to set email alerts
|

Folate‐targeted nanoparticles show efficacy in the treatment of inflammatory arthritis

Abstract: Objective To investigate the uptake of a poly(amidoamine) dendrimer (generation 5 (G5)) nanoparticle covalently conjugated to polyvalent folic acid (FA) as the targeting ligand into macrophages, and the activity of a FA- and methotrexate-conjugated dendrimer (G5-FA-MTX) as a therapeutic for the inflammatory disease of arthritis. Methods In vitro studies were performed in macrophage cell lines and in isolated mouse macrophages to check the cellular uptake of fluorescently tagged G5-FA nanoparticles, using flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
121
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(122 citation statements)
references
References 50 publications
1
121
0
Order By: Relevance
“…Several receptors such as CD44, CD64, folate receptor-beta (FR-β), vasoactive intestinal peptide (VIP) receptor, scavenger receptor class A, toll-like receptors, transforming growth factor-beta receptors, etc. were over-expressed on activated macrophages [1,[11][12][13][14][15][16].…”
Section: How To Design An Active Targeting Nanomedicine For Ra Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several receptors such as CD44, CD64, folate receptor-beta (FR-β), vasoactive intestinal peptide (VIP) receptor, scavenger receptor class A, toll-like receptors, transforming growth factor-beta receptors, etc. were over-expressed on activated macrophages [1,[11][12][13][14][15][16].…”
Section: How To Design An Active Targeting Nanomedicine For Ra Treatmentmentioning
confidence: 99%
“…Thomas et al [15] synthesized a folic acid-and methotrexate-conjugated poly(amidoamine) dendrimer (generation 5) to specifically target activated macrophages. Therapeutic effects were revealed by using CIA mice.…”
Section: Applications Of Active Targeting Nanomedicinesmentioning
confidence: 99%
“…As a result, the most potent of the selected ligands, 9-N-(4H-thieno[3,2-c]chromene-2-carbamoyl)-Neu5Acα2-3Galβ1-4GlcNAc ( TCC Neu5Ac), was conjugated to lipids for display on a liposomal nanoparticle, which later showed high level of in vivo affi nity toward Sn-positive macrophages. A review presenting some aspects of Sn structure and function and summarizing up-to-date progress on the identifi cation of sialic acid based high-affi nity ligands of certain well explored Siglec receptors has been done by Magesh et al [17].…”
Section: Sialoadhesin Receptorsmentioning
confidence: 99%
“…Furthermore, a recent study demonstrated that PAMAM dendrimers covalently linked to both folate and methotrexate could be used to selectively deliver methotrexate to synovial macrophages (Thomas et al, 2011). Although the antifolate MTX does not have a high affinity for any MFRs, several other folate analogs have been identified that possess high affinity for FR with low affinities for other MFRs and the RFC (van der Heijden et al, 2009).…”
Section: Active Targeting Strategiesmentioning
confidence: 99%